An Equilibrium Model of the African HIV/AIDS Epidemic - Jeremy Greenwood; Philipp Kircher; Cezar Santos; Michèle Tertilt (Center for Economic Studies and ifo Institute (CESifo), 2018)
Twelve percent of the Malawian population is HIV infected. Eighteen percent of sexual encounters are casual. A condom is used a third of the time. To analyze the Malawian epidemic, a choice-theoretic general equilibrium search model is constructed. In the developed framework, people select between different sexual practices while knowing the inherent risk. The calibrated model is used to study several policy interventions. The analysis suggests that the efficacy of public policy depends upon the induced behavioral changes and equilibrium effects. The framework thus complements the insights provided by epidemiological studies and small-scale field experiments.
Keywords: I18; J12; O11; O55; 330; ART; circumcision; condoms; disease transmission; epidemiological studies; HIV/AIDS; homo economicus; knowledge about HIV; Malawi; marriage; policy intervention; search; small field experiments; STDs; sex markets